Personality Traits and Classification using Machine Learning - M. Nagavamsi; Vemula Sriya; Bommidi China Babu; Koka Divya; Gajjala B.R.V.S Sailesh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Personality is one feature that determines how people interact with the outside world. Personality can be defined as a necessary element of a person’s behavior. The way people interact with other people determines their personality. This project covers the topic of Automated Personality Classification [1] – a system that analyses the personality of a user based on certain features using Data Mining Algorithms. In this project, a system is proposed which analyses the personality of an applicant. This system will be helpful for organizations as well as other agencies who would be recruiting applicants based on their personality rather than their technical knowledge. The personality prediction results are based on Big Five Personality traits and the classification is done using Naïve Bayes Algorithm and Support Vector Machine [2].